Thickness and vP/vS of sedimentary and bedrock layers in the crust in the Yuan’an Graben and their tectonic implication - Qi Deng; Zigen Wei (地震科学进展, 2025)
The Yuan’an Graben, which holds abundant shale gas, is located at the junction of the Jianghan Basin and the Huangling Block. Information about the graben’s deep structure has great significance for analysis of the basin-mountain interaction and the sedimentary response of shale gas. In this study, the thickness and vP/vS of the sedimentary and bedrock layers beneath seven temporary seismic stations in the Yuan’an Graben were obtained using the multi-layer H-κ stacking approach of receiver function. The results show that the average thickness and vP/vS of the sedimentary layer in the Yuan’an Graben are 3.68 km and 1.98, respectively. Those of the bedrock layer are 31.51 km and 1.70, respectively. The average crustal thickness is 35.19 km, and the average vP/vS is 1.73. These observations support the inference that the Yuan’an Graben has experienced thinning of the lower crust under long-term basin-mountain interaction, but the crust as a whole still maintains the characteristics of typical cratonic crust. The thickness of the sedimentary layer in the Xiakou-Yuan’an anticline zone on the west side of the Yuan’an Graben is 2.55 km, which is less than the thickness of 4.14 km of the sedimentary layer in the Xunjian-Xiqian syncline zone on the east side, which is enriching in shale gas. However, the average vP/vS of its sedimentary layer is 2.17, which is higher than 1.93 on the east side. The aforementioned results show that the tectonic environment of long-term preservation of shale gas in the anticline belt may be destroyed during the uplift and denudation process and that the vP/vS of the sedimentary layer with enriching shale gas is not necessarily higher than that in the surrounding area with a shortage of shale gas.